Association of heart diseases with COPD and restrictive lung function – Results from a population survey - Eriksson, Berne; Lindberg, Anne; Müllerova, Hana; Rönmark, Eva; Lundbäck, Bo (Respiratory medicine, 2013)
Few studies have explored the association of COPD, based on GOLD definition, with heart diseases. The relationship between restrictive lung function impairment and heart diseases is still poorly studied on a population level. To explore the association of COPD and restrictive lung function impairment, respectively, with heart diseases in the general population. This is a cross-sectional study of 642 randomly selected 22- to 72-year-old subjects in northern Sweden. COPD was defined according to GOLD. Restrictive lung function was defined as pre-bronchodilator FVC <80% of predicted value and FEV1/FVC ≥0.7. The prevalence of ischemic heart disease was 4% in subjects with normal spirometry, 13% in subjects with COPD, and 21% in those with restrictive lung function. The prevalence of heart diseases increased with COPD severity. On the other hand, the prevalence of COPD was particularly high in the group reporting myocardial infarction. In subjects reporting different heart diseases, the prevalence of restrictive lung function was high. In multivariate analyses including age, sex, smoking habits, family history of obstructive airway disease, body mass index, and socio-economic status as independent variables, COPD was associated with ischemic heart disease (odds ratio [OR] 2.61; 95% confidence interval [CI] 1.12–6.08) and ischemic heart disease with COPD (OR 2.40; 95% CI 1.03–5.61). The study shows a strong association between COPD and cardiovascular diseases and indicates a strong association between restrictive lung function and heart diseases. Both obstructive and restrictive lung function impairments were common among subjects with heart diseases and vice versa.